PENGARUH THERAPEUTIC WALKING EXERCISE TERHADAP PENURUNAN TEKANAN DARAH PADA ANAK OBESITAS USIA 9-10 TAHUN DENGAN HIPERTENSI DI SEKOLAH DASAR SARASWATI TABANAN - Made Satria Ambarsika; Nila Wahyuni; I Gusti Ayu Artini (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACT The purpose of this study was to know the effect of therapeutic walking exercise to decrease blood preassure in obesity children with hypertension 9-10 years old at Saraswati Tabanan Elementary School. This is the experimental study with Pre and Post Test Two Group Design. The amount of sample were 16 person that divided into 2 groups, one group was experimental group and the other group was control group.Normality and homogeneity test using Saphiro-Wilk Test and Levene's Test. The result of Paired Sample T-Test for blood pressure in the experimental group was obtained p = 0,000 (p <0,05) for systolic blood pressure and p = 0,010 (p <0,05) for diastolic blood pressure. In the control group, systolic blood pressure was obtained p = 0,598 (p> 0,05) and diastolic blood pressure got p value = 0,170 (p> 0,05). This shows that in the experimental group there was a significant decrease in blood pressure, whereas in the control group there was no significant decrease in blood pressure. The mean difference of decrease of blood pressure in experimental group and control group was obtained p = 0,000 (p <0,05) for systolic blood pressure data and p = 0,009 (p <0,05) for diastolic blood pressure data. Key words: Therapeutic walking exercise, obesity, hypertension